A Case of Right Alien Hand Syndrome Coexisting with Right-Sided Tactile Extinction - Schaefer, Michael; Denke, Claudia; Apostolova, Ivayla; Heinze, Hans-Jochen; Galazky, Imke (Frontiers in Human Neuroscience, 2016)
The alien hand syndrome is a fascinating movement disorder. Patients with alien hand syndrome experience one of their limbs as alien, which acts autonomously and performs meaningful movements without being guided by the intention of the patient. Here we report a case of a 74-years old lady diagnosed with an atypical Parkinson syndrome by possible corticobasal degeneration. The patient stated that she could not control her right hand and that she felt like this hand had her own life. We tested the patient for ownership illusions of the hands and general tactile processing. Results revealed that when blindfolded, the patient recognized touch to her alien hand only if it was presented separated from touch to the other hand (bilateral asynchronous touch). Delivering touch synchronously to both the alien and the healthy hand resulted in failure of recognizing touch to the alien hand (bilateral synchronous touch). Thus, the alien hand syndrome here co-existed with right-sided tactile extinction and is one of only very few cases in which the alien hand was felt on the right side. We discuss the results in the light of recent research on the alien hand syndrome.